INTERPRETATION OF TECTONIC SETTING AND MAGMATISM FOR EDUCATION AND GEOTOURISM IN IJEN UNESCO GLOBAL GEOPARK, EAST JAVA, INDONESIA - Baraas, Abdillah (Fakultas Ilmu dan Teknologi Kebumian (FITB), Institut Teknologi Bandung (ITB), 2023)
Indonesia's tectonic conditions are quite interesting, especially discussing about the boundary conditions of the western and eastern parts of Indonesia's tectonic areas which have very different characteristics. One of the things that results from tectonic activity is magmatism that produces volcanoes. The Sunda Arc in the western part of Indonesia is a subduction tectonic zone that produces arcvolcanoes. Oneof the volcanoes that grows in the areais the Ijen Volcano Complex which is in a very interesting position.It is located at the boundary or transition between the Sundalandpart in the west and the crust that thinner in the eastern part. Itsvolcanism is also quite interesting because it produces a caldera formed by an explosive eruption. The Ijen Complex grows on top of Tertiary sedimentary rocks. The magmatism is also affected by the assimilation process between sedimentary rocks and magma that comes from partial melting in the subduction zone. Knowledge regarding the interpretation of tectonic conditions and magmatism at Ijen is important as educational material. By studying the Ijen Volcano Complex, we can get data that the surface carried by magma rises and erupts so that we can obtain information about what is happening at the bottom beneath the surfacethere and its tectonic configuration.The results ofthis research are used for educational and geotourism activities in the Ijen Geopark area which are used to complete geological stories from existing sites. Key words: Interpretation, geopark, Ijen, volcano, geotourism